RETRACTED: Efficient Concentration Protocols for the Single-Photon Entanglement State with Polarization Feature - Zhou, Lan; Wang, Dan-Dan; Wang, Xing-Fu; Gu, Shi-Pu; Sheng, Yu-Bo (Frontiers in Physics, 2017)
We propose two efficient entanglement concentration protocols (ECPs) for arbitrary less-entangled single-photon entanglement state, in which the photon qubit has the polarization feature. The first ECP is in linear optics, and the second ECP is in nonlinear optics. The two ECPs have some attractive advantages. First, they can preserve the polarization feature of the photon qubit, while all the other existing ECPs for single photon state cannot achieve this goal. Second, they only require one pair of less-entangled single-photon entanglement state and some auxiliary single photons. Third, they only require local operations. Especially, the second ECP can be used repeatedly, which can increase its success probability largely. Based on above properties, our two ECPs, especially the second one may be useful in current and future quantum communication.